Insight into mature biofilm quorum sensing in full-scale wastewater treatment plants. (November 2019) - Wang, Jinfeng; Liu, Qiuju; Hu, Haidong; Wu, Bing; Zhang, Xu-xiang; Ren, Hongqiang
Abstract: Quorum sensing (QS) has been thoroughly investigated during initial biofilm formation stages, while the role of QS in mature biofilms has received little research attention. This study assessed QS in 22 biofilm samples from full-scale wastewater treatment plants in China. Results showed that the concentration of acyl-homoserine lactones (AHLs) in various biofilm bound forms, ranged from 15.63 to 609.76 ng/g. The highest concentration of AHLs was found in the tightly bound biofilm fraction, while the lowest concentrations were observed in the surface biofilm fraction. Environmental variables, C/N ratio and temperature, were found to be significant factors influencing biofilm AHL distribution ( p  < 0.01). Higher C/N ratios (ranging from 3 to 12) and low temperatures contributed to the higher concentration of AHLs in biofilms. Dominant AHLs (C10-HSL and C12-HSL) were significantly associated with biofilm activity (R 2  = 0.98/0.97, p  < 0.05), with the tightly bound biofilm fraction (TB-biofilm) presenting the highest activity (ATP concentration). Biofilm aging and re-formation processes were more active in the surface biofilm layer (S-biofilm), while the stable structure of the TB-biofilm layer which is attached to the surface of bio-carriers ensures high biofilm activity. This study furthers our understanding of the roles of AHLs in the regulation of mature biofilm activities. Graphical abstract: Image 1 Highlights: Significant differences in AHLs distribution occurred in mature biofilm fractions. The concentrations of AHLs were highest in tightly bound biofilm fractions. The concentrations of dominant AHLs were correlated with biofilm activity. Biofilm aging and re-formation processes were more active in the S-biofilm layer.